THE INFLUENCE OF GOVERNANCE ON BANKING PERFORMANCE MEDIATED BY GREEN BANKING (EMPIRICAL STUDY ON BANKS LISTED ON THE IDX 2020 – 2024) - Fadhil Muhammad Barama; Husaini; Fadli (RADJA PUBLIKA, 2026)
This study aims to analyze the influence of corporate governance on banking performance as mediated by green banking practices in banks listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. This research uses a quantitative approach with secondary data from the annual reports of 30 banks over 5 years (150 observations). Data analysis was conducted using Partial Least Square (PLS)-based Structural Equation Modeling (SEM) with SmartPLS 4.0 software. The governance variable was measured through the board of commissioners, independent commissioners, audit committee, managerial ownership, and institutional ownership. Bank performance was measured by Return on Assets (ROA) and Tobin's Q, while green banking was measured based on 16 sustainability disclosure indicators. The results show that corporate governance (except for managerial ownership and independent commissioners) has a significant effect on green banking. Green banking has a significant effect on bank performance (ROA and Tobin's Q). Green banking proves to significantly mediate the relationship between corporate governance and banking performance, both for ROA and Tobin's Q. The implementation of green banking acts as a strategic mediating mechanism in transforming good corporate governance practices into improved banking performance, both in terms of profitability (ROA) and market value (Tobin's Q). These findings highlight the need to strengthen green banking policies and strategies as part of sustainable governance in the Indonesian banking sector.